Comparative study of bupivacaine and bupivacaine plus dexamethasone under ultrasound guidance for sacral erector plane block in pediatric urological surgeries - Esmat Mundrawala; Usha Badole; Poornima Sonkamble; Sukriti Atram (Медицина болю)
BACKGROUND: sacral erecter spinae plane block is a relatively new and safe interfascial plane block for paediatric urogenital surgeries. We aimed at comparing the intraoperative and postoperative analgesic efficacy of Bupivacaine alone and Bupivacaine plus Dexamethasone in ultrasonography guided single shot sacral erecter spinae plane block for urogenital surgeries in paediatric patients under general anaesthesia.